Small Towns, Brain and Architectural Education - Bulgakova, Elena; Lidin, Konstantin (project baikal, 2019)
The number of Russian architects in relation to the country’s total population is far below the western countries and close to China and India. Most Russian cities lack their own architectural schools or communities, which makes it currently important to develop different types of the remote work with unique cultural contexts of small historic towns. The development of these types is hindered by the existing system of architectural education focused on analytical “left-brain” methods of thinking. The synthetic “right-brain” methods were actively developed in the pedagogical policies of the most creative periods in Russian architecture. It is proposed to develop and to use the methods of integrative thinking in the present-day training of architects.